PROBLEMS OF IMPROVING THE ACTIVITIES OF PUBLIC ADMINISTRATIONS IN THE SECURITY AND DEFENSE SECTOR - Shopina, I. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
The purpose of the article is to determine, based on the analysis of approaches to the effectiveness of public administrations in the security and defense sector, areas for improving the activities of these bodies. It has been established that the full-scale armed aggression of the Russian Federation against Ukraine, which caused the introduction of the legal regime of martial law, exacerbated the problems existing in the field of public administration in the security and defense sector. It is argued that public administration under the conditions of the legal regime of martial law has its own differences related to the emergence of new types of public administrations (military administrations), the restriction of certain rights and freedoms of man and citizen, and the expansion of the competence of military authorities. Particular attention is paid to the essence and characteristics of civilian democratic control over the security and defense sector. It has been determined that assessment within the framework of public supervision as an integral part of democratic civil control allows, on the one hand, to maintain objectivity due to the absence of disciplinary and other administrative ties between the subject and object of supervision. It is argued that democratic civil control should be carried out taking into account the restrictions existing in the conditions of the legal regime of wartime, related both to public activity and access to certain types of information. It has been established that the effectiveness of public administration in the civil sector and the security and defense sector has its general criteria for the quality and speed of their implementation of administrative procedures within their competence. At the same time, the subjects of assessment will differ: if in the civilian sector such subjects will be general, then in the security and defense sector they will be special. It is concluded that the directions for improving the activities of public administrations in the security and defense sector should include: a) clarifying the legal status of military administrations, the grounds and procedure for their creation; b) standardization of procedures for the transformation of military-civilian administrations into military administrations; c) establishment and normative consolidation of requirements for the educational level and professional experience of the heads of military and military-civilian administrations.